Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fbioe.2020.537847
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and Alzheimer’s Disease: Potential and Limitations of Prebiotic, Synbiotic, and Probiotic Formulations

Abstract: The Microbiome has generated significant attention for its impacts not only on gastrointestinal health, but also on signaling pathways of the enteric and central nervous system via the microbiome gut–brain axis. In light of this, microbiome modulation may be an effective therapeutic strategy for treating or mitigating many somatic and neural pathologies, including neurodegenerative disorders. Alzheimer’s disease (AD) is a chronic neurodegenerative disease that interferes with cerebral function by progressively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 109 publications
(114 reference statements)
0
46
0
1
Order By: Relevance
“…Recent studies also indicate that prebiotic and synbiotic supplementation may also have significant ability to improve metabolic activity and improve cognition in AD patients. Synbiotics showed to increase bioavailability of microbially produced antioxidant metabolites, enhancing activity of antioxidant systems and improving cognitive function among AD patients [ 155 , 156 ]. Within possible mechanisms behind AD, there is also one related to the secretory function of gut microbiota, which may modulate brain plasticity, affect cognitive function and develop AD via other than previously mentioned neurotransmitters and neuromodulators (e.g., serotonin, GABA, and histamine), or neurotoxic metabolites (e.g., D-lactic acid and ammonia) [ 38 , 113 , 131 ].…”
Section: What Are the Possible Mechanisms Behind Gut Microbiota And Dementia?mentioning
confidence: 99%
“…Recent studies also indicate that prebiotic and synbiotic supplementation may also have significant ability to improve metabolic activity and improve cognition in AD patients. Synbiotics showed to increase bioavailability of microbially produced antioxidant metabolites, enhancing activity of antioxidant systems and improving cognitive function among AD patients [ 155 , 156 ]. Within possible mechanisms behind AD, there is also one related to the secretory function of gut microbiota, which may modulate brain plasticity, affect cognitive function and develop AD via other than previously mentioned neurotransmitters and neuromodulators (e.g., serotonin, GABA, and histamine), or neurotoxic metabolites (e.g., D-lactic acid and ammonia) [ 38 , 113 , 131 ].…”
Section: What Are the Possible Mechanisms Behind Gut Microbiota And Dementia?mentioning
confidence: 99%
“…The modulation of systemic inflammatory response with prebiotics and probiotics can be part of a comprehensive approach to slow down the cognitive decline through an impact on gut-brain axis ( 122 , 123 ). A positive effect on cognitive performance for diets rich in fiber and polyphenols can partially be attributed to the prebiotic properties of the mentioned nutrients.…”
Section: Microbiota-mediated Link Between Nutrition and Alzheimer's Diseasementioning
confidence: 99%
“…Afflicted lipid metabolism could trigger neurodegenerative processes, and reversely Labarre et al have shown that dietary treatment with L. rhamnosus HA-114 restored lipid homeostasis, including energy balance via mitochondrial b-oxidation [105]. According to previously documented studies, probiotics have shown impressive ability to decelerate AD advancement due to clinically proved anti-inflammatory and antioxidant effects, including their ability to normalize cognitive deterioration that appreciably highlights their therapeutic applicability and effectiveness [106][107][108][109].…”
Section: Probiotics Involved In Obviation Of Alzheimer's Disease Progression and Amelioration Of Cognitive Conditionsmentioning
confidence: 99%
“…Of late, studies have suggested that probiotics could shape and induce balance in the microbiome and ameliorate AD symptoms via miscellaneous mechanisms [ 106 ]. Most of these mechanisms are generally assigned due to the production of antioxidants and their potential to neutralize ROS and inhibit the cytokine production of pro-inflammatory cascades [ 106 ].…”
Section: Probiotics Involved In Obviation Of Alzheimer’s Disease Progression and Amelioration Of Cognitive Conditionsmentioning
confidence: 99%